Contextualizing Forensic Nursing - de Souza, Jhuliano Silva Ramos; Resck, Zélia Marilda Rodrigues; Vilela, Sueli de Carvalho (Seven Editora, 2024)
Forensic Nursing is a specialty that combines knowledge of health, law, and criminology, focusing on the application of nursing in legal contexts. It involves gathering evidence, assisting victims of crime, and accurate documentation for court proceedings. Forensic Nurses work at the interface between health and justice, using their technical and ethical expertise. It is essential that these professionals understand the ethical, legal, and political implications of their work, respecting confidentiality, ensuring informed consent, and reporting incidents accurately. The specialty is also concerned with meeting the emotional needs of victims, considering the trauma they face. Training in this area is crucial, as nurses must have a solid understanding of healthcare practices and legislation. The integration between theory and practice is necessary to deal with complex cases and collaborate with other disciplines in the justice system, making forensic nursing a fundamental area for the protection of victims’ rights and the promotion of social justice. DOI:https://doi.org/10.56238/sevened2024.016-020